Don Vasco de Quiroga: Educator - Arce García, Victorino de (Pulso. Revista de educación, 2001)
This essay aims to demonstrate that Vasco de Quiroga, in addition to being recognised by Emperor Charles V of Spain, was a significant educator of the Tarascos (Michoacan) Natives during the sixteenth century. While he did not invent anything, he was able to actualise what others had only imagined. His approach blended the idealism of Plato and Sir Thomas More, also venerated as a saint by the Catholic Church, with the realism of a man who believed in God and nature and knew how to guide individuals towards freedom. His educational method was based on three pillars: respect for individual freedom, a holistic view of the person, and attention to individual differences, all within a Christian conception of life. The result was the emergence of "little [hospital] towns".